Enhancement of Antibacterial Agent of Cobalt Ferrite/AC/DMSO with Ferrofluid - Dea Berliana Ramadhani; Ahmad Taufiq; Sunaryono Sunaryono (Universitas Negeri Malang, 2024)
Global health is under serious threat due to antimicrobial resistance, especially in bacteria. Therefore, this study offers an alternative in the form of an antibacterial agent based on cobalt ferrite/AC/DMSO ferrofluid. This ferrofluid was successfully synthesized using the coprecipitation method, which was confirmed by XRD, SEM, FTIR characterization, and antibacterial tests. XRD results showed that cobalt ferrite nanoparticles formed an inverse cubic spinel crystal structure, and the AC material was amorphous. The particles were spherical in shape that were quite agglomerated with particle sizes of 28.5 ± 0.5 nm. Then, the formation of cobalt ferrite and AC was also confirmed by the appearance of M-O and C-O, C=O bonds. DMSO surfactant was shown with a typical bond, namely S=O. While coconut oil was detected by C-O, C=O, CH2, and CH3 bonds. Interestingly, the performance of cobalt ferrite/AC/DMSO ferrofluid is shown by the antibacterial test results which produce an inhibition zone diameter of Escherichia coli bacteria of 9.50 ± 1.01 mm.